Metacognitive sensitivity and symptoms of mental disorder: A systematic review and meta-analysis - Hohendorf, Marianne; Bauer, Markus (Frontiers in Psychology, 2023)
Metacognition is a term used to refer to cognition about cognitive processes. In this systematic review and meta-analysis, we reviewed studies that investigated the relationship between experimentally measured objective metacognitive sensitivity and diverse symptoms of mental disorder. In these studies, metacognitive sensitivity is operationalised as the correspondence between the accuracy of task performance and reported confidence therein. A literature search was conducted across four databases and studies were selected for review based on predefined eligibility criteria. Twenty studies were included in the review and separate meta-analyses were conducted for psychotic and non-psychotic categories of psychiatric symptoms. A significant reduction (medium effect size) in metacognitive sensitivity was found in individuals with psychosis-related symptoms of mental disorder compared to healthy control groups, but no significant difference was found for individuals with non-psychotic symptoms. It should be noted though, that fewer studies were available for the latter group. Sub-group analysis found no evidence that the effect of metacognitive impairment depended on whether perceptual or non-perceptual experimental tasks were employed. These findings are discussed in relation to other conceptualisations of metacognition and the role reduced metacognitive sensitivity may play in forms of mental disorder.